The Variance Risk Premium and Fundamental Uncertainty - Christian Conrad; Karin Loch (University of Heidelberg, Department of Economics, 2015)
We propose a new measure of the expected variance risk premium that is based on a forecast of the conditional variance from a GARCH-MIDAS model. We find that the new measure has strong predictive ability for future U.S. aggregate stock market returns and rationalize this result by showing that the new measure effectively isolates fundamental uncertainty as the factor that drives the variance risk premium.
urn:nbn:de:bsz:16-heidok-183127
Keywords: 330; Variance risk premium; return predictability; VIX; GARCH-MIDAS; economic uncertainty; vol-of-vol; Risikoprämie; Streuungsmaß; Kapitalmarktrendite; ARCH-Modell; USA